Usefulness of the Magnetodynamic Mallet in Tooth Extraction: A Case Series - Domenico Baldi; Francesca Baldi; Federica Giordano; Luisa De Giorgis; Francesco Bagnasco; Andrea Tancredi Lugas; Maria Menini; Jacopo Colombo (Applied Sciences)
Background: Tooth extraction techniques have been refined over the years in order to be less traumatic and to better preserve alveolar bone. A recently introduced extraction method involves the use of the Magnetic Mallet®, which allows clinicians to be more precise and perform extractions faster. Moreover, the instrument enables the procedure to be less traumatic for patients. The aim of the present study was to clinically evaluate whether extractions performed using the Magnetic Mallet® can lead to less buccolingual bone resorption. Methods: Between February 2023 and June 2023, nine patients with an average age of 62 years underwent 29 extractions using the Magnetic Mallet®. Sectorial CBCTs were performed in order to measure buccolingual bone thickness at time 0 (T0, before extraction) and 3 months after extraction (T3M). All the extractions were performed by two different expert operators exclusively using the Magnetic Mallet®. For statistical analysis, a two-sample t-test was performed to determine the difference between the measurements taken at T0 and those taken at T3M in the 29 dental elements and the difference in bone loss between the surgeries conducted by the two clinicians. Results: A total of 22 teeth were extracted in the upper jaw and 7 in the lower jaw. The average degree of mobility was 1. The average degree of force impressed by the instrument to extract the teeth was 2, while the average frequency of blows administered was 7. The average time taken for the extractions was 3½ min. After 3 months, the mean buccolingual bone resorption was 1.54 mm (SD: ±). The difference in buccolingual bone thickness between T0 and T3 was significant at an alpha significance level of 0.01. No difference in bone resorption was found between the surgeries conducted by the two clinicians. Conclusions: The use of the Magnetic Mallet® results in bone loss in the buccolingual direction comparable with existing data in the literature on healing the post-extraction socket. This tool seems to be predictable in producing the same results between different operators.